2008
DOI: 10.1021/mp700091j
|View full text |Cite
|
Sign up to set email alerts
|

A Nanoemulsion Formulation of Tamoxifen Increases Its Efficacy in a Breast Cancer Cell Line

Abstract: This paper reports on the preparation of a water-soluble nanoemulsion of the highly lipid-soluble drug tamoxifen (TAM). In addition, relative to a suspension of TAM, the nanoemulsion preparation demonstrated a greater zeta potential (increased negative charge) which has previously been associated with increasing drug/membrane permeability. This study also reports that relative to suspensions of TAM with particle sizes greater than 6000 nm, nanoemulsions of TAM, having mean particle sizes of 47 nm, inhibited ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(57 citation statements)
references
References 46 publications
4
51
0
Order By: Relevance
“…However, it may cause no significant difference between solution and nanoemulsion in the in vitro anti-tumor activity because of the continuous contact of cells with drug that dissolved in either solution or nanoemulsion. Meanwhile, it was reported that an enhanced membrane permeability or increased efficacy of drug could be achieved by the utilization of nanoemulsion owing to its decreased particle size, or interference of components in nanoemulsion with cell membrane (29,30). Therefore, it may be employed in the nuclear gene delivery systems to achieve nuclear transport of drug (31), which was further demonstrated by the fact that Nile red incorporated in the nanoemulsion could be transported into cell nucleus as showed in the present study.…”
Section: Discussionsupporting
confidence: 62%
“…However, it may cause no significant difference between solution and nanoemulsion in the in vitro anti-tumor activity because of the continuous contact of cells with drug that dissolved in either solution or nanoemulsion. Meanwhile, it was reported that an enhanced membrane permeability or increased efficacy of drug could be achieved by the utilization of nanoemulsion owing to its decreased particle size, or interference of components in nanoemulsion with cell membrane (29,30). Therefore, it may be employed in the nuclear gene delivery systems to achieve nuclear transport of drug (31), which was further demonstrated by the fact that Nile red incorporated in the nanoemulsion could be transported into cell nucleus as showed in the present study.…”
Section: Discussionsupporting
confidence: 62%
“…It is important to note, that at higher doses, both the NFP and PSD showed similar cytotoxic effects on both cell lines. These results are similar to previous work by our laboratory (25,26) with the chemotherapeutic drugs dacarbazine and tamoxifen, which also showed greater efficacy when utilized as a nanoemulsion formulation as compared to their suspension formulations in both a MCF-7 cancer cell line and a xenograft mouse model of melanoma.…”
Section: Discussionsupporting
confidence: 90%
“…Nanoemulsions are a class of stable emulsions formed by monolayers of phospholipids composed of a surfactant and oil suspended in water. The nanoemulsions are often referred to as "Approaching Thermodynamic Stability" [25,26]. Compared to typical suspension preparations which can be thousands of nanometers in size, nanoemulsion delivery systems utilized and reported from our lab, as well as those of others, with particle sizes approximately 100 nm or less have been shown to increase bioavailability and efficacy in vivo of delta and gamma tocopherol, aspirin, an antioxidant synergy formulation (ASF), and dacarbazine [22, 24, 26,].…”
Section: Introductionmentioning
confidence: 99%
“…This may be explained by, the increased number of dextran particles in our nanocarrier, increasing attachment with the CHO cell membrane more effectively, and at reduced volume of medium. The increased attachment of the cells to the dextran polymer is also likely enhanced because of the dramatic reduction in the zeta potential as a result of the formation of nanoemulsion, as we have reported previously (23,24) From these studies, we conclude that dextran based nanocarriers produced by the SANE method, can improve media utilization. Accordingly, as nanocarriers enhance medium volume requirements for maximum cell growth, these formulation techniques can be used by the biopharmaceutical application for optimizing the cell growth with reduced volume of media.…”
Section: Figuresupporting
confidence: 71%